Effect of Buckling Restrained Braces Locations on Seismic Responses of High-Rise RC Core Wall Buildings - Munir Ahmed; Shahzadi Tayyaba; Muhammad Waseem Ashraf (Shock and Vibration)
Conventionally, a flexural plastic hinge is designed and detailed at the core wall base and coupling beams ends to control the seismic responses. This strategy is based on allowing the damage to be concentrated on main structural components. To avoid such damage, an alternative strategy using energy dissipating devices (EDDs) such as buckling restrained braces (BRBs) is being studied and implemented nowadays. In this study, effect of BRBs locations on forty- (40-) story high-rise RC core wall case study building has been studied in detail using Nonlinear Response History Analysis (NLRHA) for seven spectrally matched ground motions. BRBs have been installed at critical locations identified with respect to the maximum DBE elastic modal racking shear deformation demands and force (shear and moment) demands in three different options. The force, deformation, and energy demands on structural components are compared for conventional design and different options of BRBs. The comparison with conventional design shows that BRBs not only are effective for reducing shear force demand along wall height, bending moment demand at mid height, and deformation demands by 10%, 45%, and 45%, respectively, but significantly reduce the rotation and energy demands in the core wall by 90% and 250%, respectively.